Building Information Modeling using Revit for Architects and Engineers - Makhmalbaf, Atefe (Open textbook library., 2022)
This book offers a web-based multimedia platform to enable students in Architecture, Civil Engineering, and Construction Engineering to learn fundamentals of BIM using Revit and be able to create building architectural, mechanical and structural models, develop construction documentation and analyze building performance. The platform include: book chapters on detailed Revit instructions and videos.